Obituary: An essay on the honour of Syed Muhammad Naquib al-Attas (1931-2026): EDITORIAL TA'ZIYAH (Non Peer-Reviewed) - Muhammad Taqiyuddin (Indonesian Journal of Islamization Studies, 2026)
Syed Muhammad Naquib al-Attas (5 September 1931 – 8 March 2026/at the night of 19 Ramadhan 1447), one of the most influential Muslim philosophers and intellectuals of the modern era, passed away at the age of 94, leaving behind a profound intellectual legacy that reshaped contemporary discussions on Islamic knowledge, education, and civilization. For more than half a century, al-Attas stood among the rare scholars who combined classical Islamic learning with modern philosophical inquiry. His writings and institutional work influenced generations of scholars across the Muslim world, particularly through his efforts to rethink the foundations of knowledge and education in the modern age.